MACHINE TRANSLATION IN ENGLISH LANGUAGE LEARNING: EXPLORING TEACHER AND STUDENT PERCEPTIONS IN INDONESIAN SECONDARY SCHOOLS - David Oktavianus; M. Yuseano Kardiansyah (Premise: Journal of English Education and Applied Linguistics, 2026)
The increasing presence of machine translation (MT) tools has caused both opportunities and challenges for English language education. This mixed-method case study examines teachers’ and students’ perceptions of machine translation (MT) use in a secondary school in Bandar Lampung, Indonesia. Data were gathered by a supervised Google Forms questionnaire combining closed items (n = 76; teachers n = 4; students n = 72) and open-ended responses. Descriptive analyses indicate that the major group of students (≈91.6%) used MT sometimes or often, while teachers reported moderate confidence in guiding students’ responsible use (mean = 3.25 on the reported scale). Thematic analysis of open responses generated five principal themes: (1) MT as scaffolding for comprehension and production; (2) time-saving and accessibility benefits; (3) accuracy and trustworthiness issues; (4) a tension between dependence and strategic engagement; and (5) assessment integrity and curricular guidance needs. Supervised administration improved data completeness but may have influenced some responses. Findings suggest MT is embedded in student practice and that teachers favor guided integration rather than prohibition. The study contributes context-sensitive evidence from a Southeast Asian secondary-school setting and provides recommendations for MT literacy instruction, assessment adaptations, and teacher professional development. Limitations are discussed, and directions for future research are proposed.